The particularities and major problems of minority regions in the middle and western parts of China and their developmental strategy - Luocheng Zhang (Gerhard-Mercator-Universität Duisburg, Institut für Ostasienwissenschaften, 2001)
China is a country that has a large number of minorities, who live in specific regions which are mainly located in Middle and West China. They are abundant in natural resources and are of general importance for China in strategic and ecological terms. Minorities live in relatively compact communities. Here the development in infrastructure as well as social and economic development (e.g. export-oriented economy) has been and is still slow, which has resulted in underdevelopment. To accelerate the development of these regions, priority has to be given to narrow the gap of social development, to protect the natural environment and to strengthen the facilities of infrastructure. In order to avoid conflicts in the future, specific policies in minority regions are needed.
Keywords: 330; minority regions; development problems; accelerated development; Ethnische Gruppe; Strukturschwacher Raum; Regionalpolitik; Nachhaltige Entwicklung; China